The Wanderer 13-14a: A hint of private prayer - Gabriele Cocco (Filologia Germanica)
The Wanderer 13-14a reveals that a man ought to “his ferðlocan fæste binde, / healde his hordcofan” (bind fast the closet of his  mind, to guard the chamber of his thoughts) in order to shelter his soul. This imagery of the compounds ferðloca and hordcofa recalls that of the word cubiculum in Ambrose’s exegesis on Mt. 6:6, “tu autem cum orabis intra in cubiculum tuum”, in De Cain et Abel I, 9.38, “cubiculum quod est in te, in quo includuntur cogitationes tuas, in quo versantur sensus tui”. The metaphorical portrayal of the heart as the innermost cubiculum of private prayer also occurs in some writings by Augustine. Ambrose’s elucidation on the term cubiculum concerning the cogitatio and the sensus, as well as Augustinian theology, may have influenced the poet in his lexical choice for the compound nouns ferðloca and hordcofa while attempting to portray the views the Anglo-Saxons had on the “fettered mind”.